DELAYS IN MAJOR CONSTRUCTION PROJECTS: IDENTIFYING THE POTENTIAL PROBLEMS IN THE CONTEXT OF KAZAKHSTAN - Orymbetova, Aliya (Nazarbayev University School of Engineering and Digital Sciences, 2024)
This study investigates one of the most common problems in the construction sector in Kazakhstan which is the delay of projects. The construction industry is strategically significant in Kazakhstan since it provides servicing and supporting roles to other sectors. Annual growth in the construction industry makes it a critical component of the modern economy of the country. Numerous conditions have been established by the state at the republic and local executive levels to encourage the growth of this sector. However, real-world construction projects frequently face extensive time delays during their life cycle and take longer to complete than scheduled, even with detailed planning, advanced management techniques, and critical path networks. This is because these projects are more complex and have a wider scope at different activity levels, and there are numerous practical constraints concerning labor, materials, equipment, management, environment, and effectiveness. In Kazakhstan, construction projects suffer and are affected by this problem too. The methodology of the work consists of quantitative and qualitative research methods to obtain more reliable and valuable results. Based on the literature review the survey method using a questionnaire was conducted among building professionals. The main goal is to identify the most frequent and important delay causes according to respondents' experience and opinions. The results according to responses the scope, initial duration, and budget of the projects are important and initially these factors should be discussed. Most respondents agreed that owners’ financial situations, lack of planning, coordination, and management skills, and unclear scope of the owner led to delays. Also, issues that are out of control such as force majeure, construction material supply chain problems, and increased prices affect the duration of the project. Conducting the case study method through a primarily descriptive exploration of real-life cases of delayed projects in Kazakhstan, the concepts that are beneficial in the clarification of the whole phenomenon of delays in natural settings, are presented. According to the analyzed and collected data, further understanding of the causes of delay issues has been provided, namely financial problems, poor scope definition, project complexity, etc. Mostly their impact on the country is tremendous. In addition, modern techniques that are currently and often used for delay analysis in projects and effectively calculate and predict the time extensions in Kazakhstan are discussed in the work. Nowadays, the implementation of BIM is contemporary and it transforms into a new approach as TIMCO. Results of secondary data collection methods and primary data collection methods were compared and discussed, and the main 14 causes that are widespread in the country were detected. The main goal and result of the study are to pay attention to the specialists from the country to the importance of the delays and try to prevent its causes. This study, among the most extensively discussed, introduces the primary subject in the country and gives more insights into the construction industry.
Keywords: Delays in construction projects; Delays in construction; Construction projects; Construction projects in Kazakhstan; Delays in construction projects in Kazakhstan; Causes of delays; Causes of delays in construction projects; Causes of delays in construction; type of access: embargo